Breastfeeding Mothers' Knowledge About Breast Care In Increasing Breast Milk Production - Angrainy, Rizka; Irianti, Berliana; Arefa, Damai Yati; Karlinah, Nelly (JURNAL PROTEKSI KESEHATAN, 2024)
WHO data in 2018 The rate of exclusive breastfeeding according to international figures is 50%. Indonesia's health data in 2021, the rate of exclusive breastfeeding in 2021 is 56.9%. Based on an initial survey conducted from 4 breastfeeding mothers, 3 breastfeeding mothers who do not understand about breast care to increase milk production. The purpose of this study was to describe the knowledge of breastfeeding mothers about breast care in increasing breast milk production at PMB Rosita Pekanbaru City in 2022. This study used a quantitative type with a descriptive design. The population in this study amounted to 44 people. The number of samples in this study amounted to 44 people who were taken by total sampling technique. The results of this study found that the majority of breastfeeding mothers' knowledge about breast care in increasing breast milk production was sufficient for 20 respondents (45.5%). Breastfeeding mothers are expected to seek more information about breast care to increase milk production from health workers, journals, and print media and increase good knowledge about breast care. Keywords : Knowledge, Breast Care, Breast Milk Production